2015
DOI: 10.5267/j.ijiec.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A De Novo programming approach for a robust closed-loop supply chain network design under uncertainty: An M/M/1 queueing model

Abstract: This paper considers the capacity determination in a closed-loop supply chain network when a queueing system is established in the reverse flow. Since the queueing system imposes costs on the model, the decision maker faces the challenge of determining the capacity of facilities in such a way that a compromise between the queueing costs and the fixed costs of opening new facilities could be obtained. We develop a De Novo programming approach to determine the capacity of recovery facilities in the reverse flow.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…DNP not only obtains optimal resource integration but also promotes the conceptual of strategic alliances for firm"s cooperation between each other. [39] presented the capacity determination in a closed-loop SC network when a queuing system is established in the reverse flow. Since the queuing system imposes costs, the decision maker faces the challenge to determine the capacity of facilities which represent a compromise between the queuing costs and the fixed costs of opening new facilities.They developed DNP approach to determine the capacity of recovery facilities in the reverse flow using a mixed integer nonlinear programming model integrated with the DNP and uncertainty of the parameters.…”
Section: A Historical Review Over De Novo Programmingmentioning
confidence: 99%
“…DNP not only obtains optimal resource integration but also promotes the conceptual of strategic alliances for firm"s cooperation between each other. [39] presented the capacity determination in a closed-loop SC network when a queuing system is established in the reverse flow. Since the queuing system imposes costs, the decision maker faces the challenge to determine the capacity of facilities which represent a compromise between the queuing costs and the fixed costs of opening new facilities.They developed DNP approach to determine the capacity of recovery facilities in the reverse flow using a mixed integer nonlinear programming model integrated with the DNP and uncertainty of the parameters.…”
Section: A Historical Review Over De Novo Programmingmentioning
confidence: 99%
“…Vahdani et al [31] applied queue system for a bi-objective SC problem including total costs and unforeseen transportation costs and used a robust optimization (RO) approach to face with uncertain parameters. Saeedi et al [32] developed an uncertain model for a CLSC problem and tried to set a balance between queue costs and other costs of system to determine the capacity of facilities. Vahdani and Mohammadi [33] formulated an uncertain SC problem and used queue system to decrease the processing time.…”
Section: Queue System and Uncertainty In Supply Chainmentioning
confidence: 99%
“…The constraint (31) describes that the load of a vehicle remains constant when the vehicle does not meet the retailer u. The constraint (32) shows the minimum and maximum limitation of loads for a vehicle to visit the retailors. The constraint (33) determines how many vehicles are needed to ship the returned items from retailor (w) to RC (r).…”
mentioning
confidence: 99%
“…They found that for different scenarios, a single product, single period will perform well with constant demand and uncertain returns. In another study Saeedi, Mohammadi and Torabi (2015) has studied the capacity determination in CLSC by establishing the queue system. Here the queue cost and fixed opening cost are obtained by modeling a mixed integer nonlinear programming.…”
Section: Literature Reviewmentioning
confidence: 99%